The prevalence and risk of missing outcome data in prenatal vitamin D supplemented gestational diabetes mellitus patients: a systematic review and meta-analysis protocol (Journal of Ideas in Health, 2020)
Background: Missing outcome data in clinical trials are important determinants of internal validity; however, its burden and risk in gestational diabetes mellitus (GDM) mothers supplemented with vitamin D remain poorly studied. Therefore, a systematic review and meta-analysis protocol is proposed here to study it. Methods: The English language publications, irrespective of its publication date, will be searched in electronic databases for randomized controlled trials studying the above outcome. The eligible trials will undergo the risk of bias assessment by the Cochrane tool. Data on its trial design, population characteristics, interventions compared, and the outcome will be abstracted. The prevalence and incidence (in risk ratio) of missing outcome data will be estimated meta-analytically. The statistical heterogeneity assessment will include the use of Chi2 and I2 statistics. For the explanation of any substantial heterogeneity, a meta-regression analysis will ensue. The statistical significance will be determined at P
Keywords: Gestational Diabetes Mellitus, Prevalence Study, Randomized Controlled Trial, Vitamin D, Epidemiologic Biases, India